Penerapan Hygiene Sanitasi Makanan Minuman Di Lembaga Pemasyarakatan (LAPAS) Anak - Suci Nurul Khaerani; Munawar Raharja; Rahmawati Rahmawati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2016)
Abstract: Application of hygiene and sanitation of food and drink in Lembaga Pemasyarakatan Anak (LAPAS). Lembaga Pemasyarakatan is have purpose to provide guidance to prisoner in Indonesia. The average population density Lapas the over capacity in Indonesia. Based on recent data form Kantor Wilayah Kementrian Hukum  dan Hak Asasi Manusia, the number of population in LAPAS class II A Martapura was ranked third highestof the 13 LAPAS in Kalimantan Selatan with the number of population of about 921 people. With many of population, application of hygiene and sanitation of food an drink need to be implement for the implementation of food safety. The purpose of this research was to determine how the application of the hygiene and sanitation of food and drink in LAPAS class II A Martapura. The study was conducted by observing how security measures against food, equipment, food handlers, and food holder then comparing them with  standard. The results showed thet the application of the hygiene and sanitation of food and drink in the category overall enough. For variable security measures on the equipment and food handlers in the category less, variable security measures on the food holder in the category enough, and variable security measures on the food in the category good. To the optimize application of hygiene and sanitation of food and drink in Lapas, efforts to do is add sanitation facilities food holder modify the open space, ordered food ingredients should not use the car open  and do not slam, washed equipment performed with the correct phases and use soap, and stroge equipment stored in a safe place to minimize contamination of biological, physical, chemical. Keywords   : Application  Higiene and sanitation of food and drink